(untitled) (Indian Journal of Public Health Research & Development, 2020)
Aim: The aim of this study was to investigate the prevalence of flare up post endodontic treatment in diabetes mellitus (DM) patients and compare between the controlled and un controlled diabetic patients and to examine the effect of glycemic control on the prevalence of flare ups. Materials and Method: A study was conducted of convenience sampling among 20 diabetic patients from a private dental clinic who had underwent Root canal treatment in the past one year and their post RCT radiographs and glycemic status were collected in order to correlate the success and failure of endodontic treatment. Result: The prevalence of periapical pain was higher in uncontrolled diabetic group than in the controlled diabetic group (13.5 vs 11.9% respectively) this difference was statistically significant (p = 0.000). The poorly controlled DM group had a higher prevalence of the restored tooth being extracted post complications compared with the well-controlled DM group (18.29 vs 9.21 respectively). This difference was statistically significant (p = 0.000). Conclusion: This survey therefore demonstrates a higher prevalence of flare ups in uncontrolled diabetic patients compared with controlled diabetic group, with an increased prevalence of persistent chronic apical periodontitis. Compared with a well-controlled diabetic group, a poor glycemic control may be associated with a higher prevalence of Apical Periodontal disease and increased rate of endodontic failures.